Skutki akcesji Polski do Unii Europejskiej w ocenie głównych Kościołów chrześcijańskich w RP - KUSZTAL, Aleksandra (Przegląd Politologiczny, 2018)
Polish membership of the European Union became a fact in 2004. The fears and hopes of the main Christian churches in Poland as regards its consequences have already been at least partly verified. This verification has been partly positive, as the main Christian churches in Poland have obtained access to direct subsidies for arable land owners. However, there have also been disappointments, such as the disappointed hopes of the churches of minor denominations to obtain more balanced and actual equality of rights for different churches and religious denominations in Poland by virtue of Community law. Another disappointment concerned the expectation that due to their participation in integration processes Poles would abandon a certain religious and spiritual provincionalism, or their complete disregard of the opinions of representatives of churches and religious denominations in the process of the EU’s internal reforms. It can be observed that the intellectual and moral potential of such important institutions of social life as Christian churches in Poland has not been taken full advantage of in the European debate and discussion on integration. Unfortunately, it is also rather difficult to find any signs that this may happen in the future.